A Case Study on the Social Interaction with the Opposite Sex of Early Adult Women Raised by Single Mothers Since Childhood (Without a Father) - Salsabila, Syifa; Nurlita, Nurul (International Journal of Social Science, Education, Communication and Economics, 2025)
This research uses a case study methodology to examine the social interactions of early adult women raised in single-parent households where the father figure has been absent since childhood. Data were collected through interviews, observations, and field notes. The study reveals that the informants had strong attachments to their fathers and experienced deep grief upon their fathers' deaths, which led to social withdrawal and reluctance to engage with the opposite sex. The absence of a father figure significantly impacted the informants' social development, particularly in forming relationships with the opposite sex. Informants expressed feelings of loss and were reluctant to open up to others, especially men, due to their grief and a sense of abandonment. Despite these challenges, the informants eventually adapted by accepting the reality of their father’s death, finding comfort in spiritual growth and learning to accept themselves. This study highlights the long-lasting effects of father absence on social behaviors, particularly in early adulthood, and how these individuals navigate their relationships with others.